Reliability of expert interpretation of retinal photographs for the diagnosis of toxoplasma retinochoroiditis. Issue 6 (1st June 2002) - Stanford, M R; Gras, L; Wade, A; Gilbert, R E
Abstract : Aims: To measure agreement and estimate sensitivity and specificity of uveitis experts' interpretation of retinal photographs for the diagnosis of toxoplasma retinochoroiditis. Methods: The authors collated 96 retinal photographs from patients presenting with symptomatic posterior uveitis to ophthalmology clinics within a defined geographical area. Five uveitis experts independently ranked each photograph as definite, probable, possible, or not toxoplasma retinochoroiditis. They measured interobserver agreement based on an intraclass correlation coefficient and estimated sensitivity and specificity for each observer using a maximum likelihood model Results: The intraclass correlation coefficient for all five observers was 0.62 (95% CI: 0.54 to 0.69). Estimates of sensitivity and specificity for individual observers ranged from 71% to 96% and 58% to 100% respectively when appearances were dichotomised as definite or probable toxoplasma retinochoroiditis, versus possible or not. Conclusion: Agreement between uveitis experts on the interpretation of retinal photographs was moderate to good, but the estimates of sensitivity and specificity of their interpretation for the diagnosis of toxoplasma retinochoroiditis were highly variable. Assuming that interpretation of photographs is similar to real time ophthalmoscopy, clinicians need to beware that treatment decisions made on the basis of a single assessment will include patients without toxoplasma retinochoroiditis and will miss patients with the disease.